Sistem Informasi Penjualan Hewan Qurban Berbasis Web Menggunakan Metode Rapid Aplication Development (RAD) - Fadlurrohman, Muhammad Shiddiq; Hadikristanto, Wahyu; Widodo, Edy (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The Al-Muslim Foundation is an organization that carries out the process of selling sacrificial animals, but still uses traditional methods such as recording orders, payments and animal information manually using books or physical records. This has the potential to cause recording errors and data loss, which makes it very possible for errors to occur in the process. This research aims to build a web-based system to help handle this problem. The system that will be created uses the Rapid Application Development method. Testing of this system will be carried out using the black box testing method. The results of this research show that the Al-Muslim Foundation has succeeded in increasing effectiveness and efficiency in the process of selling sacrificial animals, as well as expanding sales so that they can be accessed by potential buyers anytime and anywhere.